PS-C29-3: CHANGE OF PANCREAS VOLUME AND GLUCOSE METABOLIC INDEX WITH THE INCREASE OF WEIGHTS: ANALYSES OF COMPREHENSIVE HEALTH CHECKUP DATA. (January 2023) - Sunouchi, Maria; Inaishi, Jun; Shimizu, Ryoko; Saisho, Yoshifumi; Takaishi, Hiromasa; Itoh, Hiroshi
Abstract : Objective: Pancreas volume measured using imaging techniques has been shown to be increased in subjects with obesity and reduced in subjects with diabetes. Beta-cell mass of pancreas also was reported to be increased with obesity in autopsy samples. While, the increase in beta-cell mass of pancreas with obesity was reported to limit in Japanese autopsy studies, suggesting that Japanese have less compensatory changes of beta-cell associated with insulin resistance. Therefore, we aimed to explore the changes of pancreas volume and glucose metabolic index including beta-cell function with the increase of weights in analyses of comprehensive health checkup data. Design and method: We collected subjects to have the following characteristics: 1) had our health checkup between April 2014 and March 2015 at aged 20–80 years; 2) had our health checkup between April 2015 and March 2017 with an increase in body mass index (BMI) of at least 1 kg/m 2 from the baseline period; 3) no diagnosis of diabetes (HbA1c < 6.5%, fasting plasma glucose < 126 mg/dl and no medication); 4) had the adequate quality in CT images to assess the pancreas volume. The pancreas was outlined by hand in each CT image and the pancreas volume was computed by summing the product of pancreas area (cm 2 ) of each image and the CT section thickness. Homeostasis model assessment of insulin resistance (HOMA-IR) and beta-cell function (HOMA-beta) were calculated as indices of insulin resistance and beta-cell function, respectively. Paired t-test was used to analyze changes in parameters. Results: Thirty-five subjects (29 men, mean age 59 years, mean height 167 cm, mean weight 71 kg) were included in this analysis and mean follow-up was 21 months. BMI and HOMA-IR increased significantly from the baseline (25.5 kg/m 2 vs. 27.0 kg/m 2, P < 0.001 and 1.58 vs. 1.89, P < 0.05). While, there were no significant change in HOMA-beta and blood pressure from the baseline (56.4 vs. 65.7 and 122/79 mmHg vs. 126/82 mmHg, all P > 0.05). Conclusion: The change in beta-cell function with the increase of weights and insulin resistance was modest, consistent with the change of beta-cell mass with obesity in Japanese autopsy samples. We report the change of pancreas volume evaluating with CT image in addition to these results.